2019
DOI: 10.1136/bmjopen-2019-030330
|View full text |Cite
|
Sign up to set email alerts
|

Using the General Social Survey – National Death Index cohort to study the relationship between neighbourhood fear and mortality in the USA

Abstract: ObjectivesFear of crime is associated with adverse mental health outcomes and reduced social interaction independent of crime. Because mental health and social interactions are associated with poor physical health, fear of crime may also be associated with death. The main objective is to determine whether neighbourhood fear is associated with time to death.Setting and participantsData from the 1978–2008 General Social Survey were linked to mortality data using the National Death Index (GSS-NDI) (n=20 297).Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This provides additional support for the value of more longitudinal research on these topics. On the other hand, another study examining the effect of perceived neighborhood safety on mortality did find a stronger and more significant association among males [35], so there is some support in other areas that perceived neighborhood safety may have a stronger effect among males.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This provides additional support for the value of more longitudinal research on these topics. On the other hand, another study examining the effect of perceived neighborhood safety on mortality did find a stronger and more significant association among males [35], so there is some support in other areas that perceived neighborhood safety may have a stronger effect among males.…”
Section: Discussionmentioning
confidence: 98%
“…More broadly, the literature shows that perceptions of an unsafe neighborhood are associated with a host of negative health outcomes while positive neighborhood safety perceptions are associated with health benefits. Poor perceived neighborhood safety is associated with more depression [29,30], reductions in walking [31,32], functional decline [33], worse health [29], and mortality [34,35] among older adults. On the other hand, perceptions that neighborhoods are safe are associated with improved psychological wellbeing [36] and increased leisure-time physical activity [37] among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to two reasons: on the one hand, physiology is understood as an inevitable outcome of psychological influences; on the other hand, FoC itself is interpreted as a social issue. Nonetheless, some researchers have found that high FoC can directly affect an individual's physical health, leading to adverse health outcomes (Grinshteyn, Muennig, & Pabayo, 2019). For instance, individuals are more likely to experience stomach discomfort, somatic issues (Jackson & Stafford, 2009: pp.…”
Section: Discussion Significance Of the Degree Of Fear Of Crimementioning
confidence: 99%
“…17,18 Neighbourhood fear has even been associated with increased mortality among males. 19 In addition, fear of crime has been associated with reduced physical well-being, as well as with poor self-reported health. [10][11][12] Fear of victimization has an inverse relationship with mental health status among older adults in China and the UK with higher levels of fear associated with worse mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Neighbourhood fear has even been associated with increased mortality among males. 19 In addition, fear of crime has been associated with reduced physical well-being, as well as with poor self-reported health. 1012…”
Section: Introductionmentioning
confidence: 99%